Delta Variant of Covid-19 Study, and Why it is a Concern: An Overview - (:unkn) unknown (AMG Transcend Association, 2021)
COVID-19 is caused by the virus SARS-CoV-2 that belongs to the Coronaviridae groups. The subgroups of the coronavirus families are α , β , γ , and δ coronavirus (the four general human coronaviruses). Representative coronaviruses consist of NL63 coronavirus (human) and porcine transmissible gastroenteritis from the Alphacoronavirus genus; mouse hepatitis coronavirus (MHV), bovine coronavirus (BCoV), severe acute respiratory syndrome coronavirus (SARS-CoV), and Middle East respiratory syndrome coronavirus (MERS-CoV); avian infectious bronchitis virus (IBV); and porcine δ -coronavirus (PdCoV). This work exhibits, δ -coronavirus spikes are fundamentally and evolutionally more similar related to α -coronavirus spikes than to β -coronavirus or γ -coronavirus spikes due to the receptor recognition, membrane fusion phenomenon, and immune evasion behavior.
Keywords: 3. Good health